'You can't really control life': dis/assembling self-knowledge with self-tracking technologies. Issue 2 (4th May 2019) - Bergroth, Harley
ABSTRACT: This article investigates everyday self-tracking as a practice of self-related knowledge production. Self-tracking activities are commonly narrated and imagined as productive of self-related knowledge and insight into one's life and bodily functions. However, by drawing from qualitative interviews with Finnish self-trackers, the article argues that in practice self-tracking also appears as prescriptive of uncertainty. The article shows how everyday self-tracking systems actively produce their functionality as systems of knowledge production in practice, as selves are extended in time and potentialized via the measurement-related affordances of self-tracking technologies. Thus, self-tracking often prescribes and animates repetitive behaviour of keeping track; of attaining experiences of self-knowledge and control which nevertheless remain elusive and flow away. The paper engages with Bernard Stiegler's discussions on temporal flux and cinematic time in order to theorize self-tracking as a practice in and through which the self is produced and lived as perpetually 'unfolding'.